Pengaruh Partisipasi terhadap Kepuasan Pemakai dalam Pengembangan Sistem Informasi dengan Kompleksitas Tugas, Komplekstas Sistem, an Pemakai sebagai Moderating Variable - Nurika Restuningdiah, Nur Indriantoro (IAIKAP, 2000)
The relationship between user participation and user satisfaction in the system development process still becomes the interesting problem, because there has not been consistent empirical result. In seeking to explain such equivocal results, the effect of three contingency factors- task complexity, system complexitu, and user influence- on the relationship between user participation and user satisfaction were investigated. As suggested in the literature, this research tests hypotheses that these spesific contingency factors should aid in identifying situations here user participation would have a strong relationship with satisfaction. Analysis of 102 midle managers from differnt organization, who become the respondents, indicated that user participation has direct relationship with user satisfaction. The cintigency factors were found to play key roles on this relationship. Task complexity and system complexity proved to be quasi moderator, so that in the high level of task and system complexity proved to play key roles on this relationship. Task complexity and system complexity, the relationship between user participation and user satisfaction was significantly stonger than in project where task and system complexity was low. User influence was shown to be quasi moderator on the relationship between user participation and user satisfaction. The implications of this stud is relevant to system developers and to academicians seeking to explain how and why user parcitipatio is needed. The results help explain the relationship between user participation and user satisfaction by sugesting the nature of the relationship under different sets of conditions.